Methods of enhancing the sustainability and scale of community based disaster risk management - Venton, Paul (Cranfield University, 2008)
Disasters are always local in their impact, and therefore approaches towards their alleviation need to be designed and implemented based on this certainty. So this research is designed to investigate methods of enhancing the development, sustainability and scale of community based disaster risk management (CBDRM). This is undertaken with a special focus upon community risk assessment (CRA) and its relationship with disaster risk reduction (DRR). Action Research (AR) is the methodological approach adopted to investigate three primary research objectives: • To investigate the link between community risk assessment (CRA) and community based disaster risk management (CBDRM). • To identify key issues when addressing the underlying causes of vulnerability within community based disaster risk management (CBDRM). • To identify challenges in enhancing the sustainability and scale of community based disaster risk management (CBDRM) through stakeholder partnership. The AR carried out has three main components: 1. The development and testing of a CRA methodology. 2. The identification of good practice CBDRM. 3. Supplementary semi-structured interviews. Perspectives on the research objectives are collated from a broad array of international experiences, but with the primary location of fieldwork in Bihar, India. Conclusions to the research demonstrate the importance of linking government policy and practice on DRR with CBDRM, and addressing the underlying causes of vulnerability. While important in their own right, these subjects have also been considered in terms of their inter-connectedness with one another. Indeed they are shown to be mutually reinforcing. However, even more pivotal is the emphasis on their relationship with CRA. Furthermore, contrary to much practice CRA, engaging government officials from the outset and incorporating an investigation into the underlying causes of vulnerability, must not be segregated from action planning but must be fully synchronised with a CBDRM process.